2010
DOI: 10.1016/j.neurobiolaging.2010.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Subregions of the inferior parietal lobule are affected in the progression to Alzheimer's disease

Abstract: Changes in several regions within the brain have been associated with progression from healthy aging to Alzheimer's disease (AD), including the hippocampus, entorhinal cortex, and more recently, the inferior parietal lobule (IPL). In this study, the IPL was divided into three subregions: the gyrus, the banks of the sulcus, and the fundus to determine if these regions are independent of medial temporal regions in the progression of AD. Participants of the Alzheimer's Disease Neuroimaging Initiative (ADNI; n=54)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 47 publications
6
62
0
Order By: Relevance
“…In prodromal AD the PCC, IPL, and RSC form a main cluster. The role of these three parietal regions indicating a prodromal AD-related assembly of posterior parietal regions is well established in AD [23,88,89]. This suggests that these regions segregate from remaining DMN nodes in prodromal AD, potentially resulting from the high metabolic activity and accumulation of amyloid plaques [22,90,91].…”
Section: Disrupted Functional Coupling Of Prefrontal and Parietal Dmnmentioning
confidence: 94%
“…In prodromal AD the PCC, IPL, and RSC form a main cluster. The role of these three parietal regions indicating a prodromal AD-related assembly of posterior parietal regions is well established in AD [23,88,89]. This suggests that these regions segregate from remaining DMN nodes in prodromal AD, potentially resulting from the high metabolic activity and accumulation of amyloid plaques [22,90,91].…”
Section: Disrupted Functional Coupling Of Prefrontal and Parietal Dmnmentioning
confidence: 94%
“…For instance, Liang et al (2012) showed that the AG connectivity with the DMN was significantly reduced in mild cognitive impairment. Another recent study also suggested that the subregions of the IPL were differentially affected in the progression from mild to severe Alzheimer's disease (Greene and Killiany, 2010). Characterizing the functional connectivity of these subregions would further our understanding of the functions of the IPL and shed new lights on how dysfunctions of the IPL may contribute to the clinical manifestations of these neurological processes.…”
Section: Potential Clinical Implicationsmentioning
confidence: 98%
“…Structural and functional abnormalities of the IPL were observed in many neurological conditions, including Alzheimer's disease (Greene and Killiany, 2010;Hanggi et al, 2011;Nelson et al, 2009;Neufang et al, 2011;Xia and He, 2011;Zahn et al, 2005) and mild cognitive impairment (Chong and Sahadevan, 2005;Greene and Killiany, 2010;Hamalainen et al, 2007;Hanggi et al, 2011;Liang et al, 2012;Markesbery et al, 2006;Walker and Walker, 2005). For instance, Liang et al (2012) showed that the AG connectivity with the DMN was significantly reduced in mild cognitive impairment.…”
Section: Potential Clinical Implicationsmentioning
confidence: 99%
“…Resting-state functional connectivity (rs-fc-fMRI) can investigate significant alterations of brain plasticity (Lewis et al, 2009) and also changes caused by the transition from healthy aging to AD (Greene and Killiany, 2010). The major advantage of restingstate-fMRI (rs-fMRI) is the reduction of the effects of inter-individual variability and behavioral performance during cognitive tasks (Ferreira and Busatto, 2013).…”
Section: See Article Pages Xxx-xxxmentioning
confidence: 99%